Loan delinquency in private sector banks in Kerala - Bosco K, Jithin; Sudha, B. (Edelweiss Applied Science and Technology, 2024)
The Indian Banking Sector faces significant difficulties in recovering debt. The banker must understand the underlying causes of loan delinquency to address the problem efficiently. A delinquent loan becomes a NPL (Non Performing Loan) when the borrower failed to repay the loan for a period of 90 days or more. Delinquency is the sign of increased credit risk, warnings of willful default, poor asset quality management and operational inefficiency. It may help to predict the loan loss provision for the sub standard, doubtful and loss assets. This article explores the various causes of loan delinquencies of private-sector banks operating in Kerala. The analysis revealed that the retails and SMEs registered high level of loan delinquency. A significant difference was found between the old and new generation private sector banks for the Poor loan portfolio management, inadequate collateral, inadequate monitoring and follow-up. From the mean score it is evident that the NPA management in new generation private sector banks is appreciable when compared to old generation private sector banks.